A Primer for Preventing Teen Dating Violence? The Representation of Teen Dating Violence in Young Adult Literature and Its Implications for Prevention. (December 2017) - Storer, Heather L.; Strohl, Katyayani R.
Teen dating violence (TDV) is a significant public health issue. Preventing TDV requires attention to risk and protective factors across ecological system levels. The media is one of the primary cultural drivers of societal-level social scripts about the causes of TDV. Framing theory asserts that the media's portrayal of social issues, including what contextual information is included and/or excluded, affects individual-level attitudes about TDV and potential policy responses. This study investigates the representation of TDV in young adult (YA) literature, a media genre that is marketed to adolescent audiences. Data include all YA novels ( N = 8) that have a primary focus on TDV. Texts were analyzed systematically using thematic content analysis methods. Results indicate that the antecedents of TDV were portrayed as being related to victim personal characteristics such as inexperience in relationships and low self-esteem. Rather than underscoring how societal-level factors contribute to TDV, perpetration was seen as stemming from family dysfunction and mental health issues. These results underscore how the structural determinants of TDV have been overshadowed in the media's portrayal of TDV, in favor of narrow portrayals of victimization and perpetration. Implications for TDV prevention programs including the importance of media literacy are discussed.